Case report: Abomasal ulcer secondary to congenital pyloric and duodenal stenosis in a 3-day-old heifer - Laabouri, Fatima Zahra; Folmar, Chelsea; Reyes, Vicente Avila; Beasley, Erin; Ryan, Clare; Brown, Corrie (Frontiers in Veterinary Science, 2023)
Abomasal ulcers, an economic concern for all calf-raising farms, are usually silent until perforation occurs, at which time management is complicated and often unrewarding. This case study describes a perforating ulcer in a 3-day-old Brahman heifer, occurring secondary to a congenital narrowing of the pylorus and proximal duodenum and leading to marked abomasal distention, leakage, and eventual peritonitis and sepsis.